Comments on "M.S. Wu, a pressure loaded soft functionally gradient spherical capsule under finite deformation", mechanics of materials, 150 (2020) 103573. (April 2021) - Batra, R.C.
Highlights: Develops mechanics solutions for pressure-loaded soft functionally gradient spherical capsule. Potential application in the mechanical design of soft robots and medical devices. Modeling incorporates second-order elasticity. Two material gradients can be used to tailor the displacements and the stress distribution.